Relationships between declarative pointing and theory of mind abilities in 3- to 4-year-olds. Issue 3 (4th May 2017) - Cochet, Hélène; Jover, Marianne; Rizzo, Cécile; Vauclair, Jacques
Abstract: The current study explored the relationships between declarative pointing and theory of mind abilities in 30 children between 3 and 4 years of age. Measures used to examine theory of mind (ToM) included a parental questionnaire and the Scaling of Theory of Mind Tasks . Results showed a dissociation between expressive and informative pointing, which have been regarded as two subcategories of the declarative function. ToM abilities were significantly related to the production of informative pointing, but not to the production of expressive pointing. This distinction might be explained by special features associated with informative pointing, such as early signs of cooperation abilities. Our results might have key implications for psychologists, as they may help improve evaluation and intervention programs for the development of social skills in preschoolers.